Evaluation of post-harvest coffee to conform with good manufacturing practices (GMP) to develop entrepreneurship. Issue 1 (April 2020) - Prajogo, U; Lutfi, M; Liana, Y; Adi, S
Abstract: Coffee has good prospects in agroindustry despite overproduction worldwide. Indonesia is ranked 4 th in the world 's main coffee producer after Brazil, Vietnam, and Colombia. One of the regencies of coffee-producer regions is Ngawi Regency which is located on the slopes of Lawu Mount. Coffee quality is the main criterion to compete with other coffee producers. The way to improve the quality of Indonesian coffee is by upgrading post-harvest handling processes. The aim of this study was the evaluation of the process of post-harvest coffee to conform with GMP (Good Manufacturing Practises) to develop farmers entrepreneurship. The research respondents were 50 coffee farmers obtained by purposive sampling method. The results showed that coffee farmers in Ngrambe Subdistrict, Ngawi District, use the dry process in the process of stripping coffee beans (81.35%). The quality of the coffee picking process is low (53.62%). Generally, coffee farmers do not sort (71.23%). The coffee storage process is also low (52.35%). The efforts required to follow up this research including the dissemination of post-coffee harvest technology that is in accordance with GMP. Furthermore, it can improve the competitive advantages of the product.